(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In 1995, public programs were transferred to Aragon to stimulate entrepreneurshipby financially supporting the creation of small and medium companies, including Cooperatives and Labour Societies. This paper analyzes the mentioned public programs and compares the survival of companies founded with or without public subsidies in Zaragoza. The result shows that companies founded without public subsidiessurvive a lower percentage than companies founded with public subsidies.